2020
DOI: 10.21082/jti.v44n2.2020.141-153
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Performance and Economic Benefits of Sugarcane (Saccharum officinarum L.) Under Drip Irrigation for Sandy and Clay Soils in East Java, Indonesia

Abstract: <p class="teksabst"><strong>Abstract.</strong><em> </em>Sugarcane (<em>Saccharum officinarum</em> L.) growth and production are greatly affected by water availability. The lack of water availability in sugarcane cultivation can be surmounted by irrigation. In performing irrigation, it is essential to understand the sugarcane crop water requirement and soil texture as they influence the irrigation efficiency. To date, drip irrigation is considered as the most efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…N content became the main limiting factor in soil with light P and K content, while P and K became limiting factors on sandy land for shallot. The site's study has similar characteristics to sandy land in Kediri, Indonesia, which showed slightly acidic pH, very low C organic content, and very low N, but with low P and K [39]. Another report analyzing coastal sandy land in the same regency as this study site (Bantul, Yogyakarta) showed similar low C organic and very low N content, varying P and K content.…”
Section: B Experiments 1: Land Suitability Analysissupporting
confidence: 54%
See 1 more Smart Citation
“…N content became the main limiting factor in soil with light P and K content, while P and K became limiting factors on sandy land for shallot. The site's study has similar characteristics to sandy land in Kediri, Indonesia, which showed slightly acidic pH, very low C organic content, and very low N, but with low P and K [39]. Another report analyzing coastal sandy land in the same regency as this study site (Bantul, Yogyakarta) showed similar low C organic and very low N content, varying P and K content.…”
Section: B Experiments 1: Land Suitability Analysissupporting
confidence: 54%
“…Previous analysis has shown that sandy physical texture and chemical properties such as total N, CEC, and exchangeable Al influenced the number of clumps per shallot plant. Dhanalakshmi et al [39] and Neina [40] reported similar results in India. A study by Sutardi [35] concluded that ameliorant application on planting media increased the percentage of silt fraction (0.55% to 2.37% change) and clay (0.45-0.51%), followed by P2O5 levels and reduced the sand content (1.05-2.07%).…”
Section: B Experiments 1: Land Suitability Analysismentioning
confidence: 60%
“…Rainfed irrigation was used in this study to evaluate its impact on water balance and agricultural production to surface irrigation. Furrow irrigation was employed since it is a conventional and more common agricultural water supplying method in Indonesia [11], while drip irrigation was implemented as the most water efficient irrigation method [12]. Each irrigation method was simulated by three field management scenarios, i.e.…”
Section: B Field Management Scenariosmentioning
confidence: 99%
“…Planting schedule was also arranged at the beginning of dry season on April, based on existing sugarcane cultivation practices in Pasuruan Regency (9). A previous research was carried out at Pasuruan to examine soil characteristics on sugarcane plantations (10). Soils of Pasuruan are classified as clay soils in general.…”
Section: Geographical Characteristics Of Pasuruan Regencymentioning
confidence: 99%
“…In this study, rainfed irrigation was introduced to compare its influence on water balance and crop yields to surface irrigation methods. Specifically, furrow irrigation was used in Scenario 2 since it is recognized as conventional method in Indonesia (11) and drip irrigation was introduced as most water efficient irrigation method in Scenario 3 (10). Initial soil water content for all scenarios were assumed at field capacity since dry season was just started on the April.…”
Section: Field Management Scenariosmentioning
confidence: 99%